Niemann-Pick disease A or B in four pediatric patients and SMPD1 mutation carrier frequency in the Mexican population - Magdalena Cerón-Rodríguez (Annals of Hepatology, 2019)
Introduction and Objectives: Niemann-Pick disease type A (NPD-A) and B (NPD-B) are lysosomal storage diseases with a birth prevalence of 0.4–0.6/100,000. They are caused by a deficiency in acid sphingomyelinase, an enzyme encoded by SMPD1. We analyzed the phenotype and genotype of four unrelated Mexican patients, one with NPD-A and three with NPD-B. Patients and methods: Four female patients between 1 and 7 years of age were diagnosed with NPD-A or NPD-B by hepatosplenomegaly, among other clinical characteristics, and by determining the level of acid sphingomyelinase enzymatic activity and sequencing of the SMPD1 gene. Additionally, a 775 bp amplicon of SMPD1 (from 11:6393835_6394609, including exons 5 and 6) was analyzed by capillary sequencing in a control group of 50 unrelated healthy Mexican Mestizos. Results: An infrequent variant (c.1343A>G p.Tyr448Cys) was observed in two patients. One is the first NPD-A homozygous patient reported with this variant and the other a compound heterozygous NPD-B patient with the c.1829_1831delGCC p.Arg610del variant. Another compound heterozygous patient had the c.1547A>G p.His516Arg variant (not previously described in affected individuals) along with the c.1805G>A p.Arg602His variant. A new c.1263+8C>T pathogenic variant was encountered in a homozygous state in a NPD-B patient. Among the healthy control individuals there was a heterozygous carrier for the c.1550A>T (rs142787001) pathogenic variant, but none with the known pathogenic variants in the 11:6393835_6394609 region of SMPD1. Conclusions: The present study provides further NPD-A or B phenotype-genotype correlations. We detected a heterozygous carrier with a pathogenic variant in 1/50 healthy Mexican mestizos.